Islamic FinTech Adoption Sharia Compliance Gender Trust - Avrila Pradita, Nasiva; Daryono (Journal International Economic Sharia, 2025)
Objective: This study looks at how technology, religion, and gender all play a part in how people use Islamic FinTech, and suggests and tests a way of thinking about it.Methods: A sample of active Islamic FinTech users was purposively selected and given a structured online questionnaire to complete. Multiple regression and multi-group analyses were used to test the direct, moderating, and gender-moderated effects within the hypothesized model.Results:  The findings confirm that perceived usefulness is a significant driver of adoption intensity. So is perceived religious compliance. And digital financial literacy. Trust in providers was found to significantly strengthen the relationships between perceived usefulness and religious compliance with usage. Crucially, the analysis revealed profound gender differences, showing that the effects of religious compliance and the moderating role of trust were significantly stronger for female users.Novelty: A unique paradigm is introduced by this research through the integration of the philosophical principles of Sharia compliance into a conventional technology adoption model, with gender being introduced as a core theoretical moderator rather than a mere control variable, thereby challenging homogeneous adoption assumptions.Research Implication: The investigation provides a substantiated, gender aware model for comprehending Islamic FinTech acceptance, delivering pivotal understandings for formulating diversified tactics that strike a chord with the unique spiritual and emotional motivators of diverse user categories, thus boosting financial integration.